2007
DOI: 10.2174/092986607781483688
|View full text |Cite
|
Sign up to set email alerts
|

The Lysozyme from Insect (Manduca sexta) Is a Cold-Adapted Enzyme

Abstract: Enzymatic activity is dependent on temperature, although some proteins have evolved to retain activity at low temperatures at the expense of stability. Cold adapted enzymes are present in a variety of organisms and there is ample interest in their structure-function relationships. Lysozyme (E.C. 3.2.1.17) is one of the most studied enzymes due to its antibacterial activity against Gram positive bacteria and is also a cold adapted protein. In this work the characterization of lysozyme from the insect Manduca se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…HSPs are produced as a protective response by cells to a variety of stress factors. The major physiological functions of the Hsp70 superfamily’s members are protein folding, unfolding and translocation [41]. Hsp70s are the most conservative and important subfamily and they are the most sensitive in responding to stress.…”
Section: Discussionmentioning
confidence: 99%
“…HSPs are produced as a protective response by cells to a variety of stress factors. The major physiological functions of the Hsp70 superfamily’s members are protein folding, unfolding and translocation [41]. Hsp70s are the most conservative and important subfamily and they are the most sensitive in responding to stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, these proteases are poorly studied in insects' innate immune systems. The insect's immune response is mediated by pattern recognition proteins that signal to expression effectors, including the antibacterial lysozyme protein [81], [82]. We found that lysozymes comprise important antimycotic enzymatic activities, as noted by its antiviral or antibacterial activity in many in vitro studies.…”
Section: Discussionmentioning
confidence: 94%
“…We observed the remarkable over-expression of lysozymes in all microconidia treatments in comparison to the controls. It appears that lysozymes take on other roles besides degrading the bacterial cell wall, and it has been shown that this protease inhibits the enzymatic activity of mosquito phenoloxidase, thereby modulating melanization [82], [83].…”
Section: Discussionmentioning
confidence: 99%
“…Lysozyme was also up-regulated, which is a well-known anti-bacterial enzyme, and is cold-adapted to work in insects dwelling at lower temperatures [73]. Melanization is an important physiological change occurring inside hemocoel when an insect is invaded by a pathogen, for example, Beauveria .…”
Section: Fusarium As An Entomopathogenmentioning
confidence: 99%